Prevalence and Diversity of Antibiotic Resistant Escherichia coli From Anthropogenic-Impacted Larut River - Bong, Chui Wei; Low, Kyle Young; Chai, Lay Ching; Lee, Choon Weng (Frontiers in Public Health, 2022)
Aquatic environments under frequent anthropogenic pressure could serve as reservoirs that provide an ideal condition for the acquisition and dissemination of antibiotic resistance genetic determinants. We investigated the prevalence and diversity of antibiotic resistant Escherichia coli by focusing on their genetic diversity, virulence and resistance genes in anthropogenic impacted Larut River. E. coli abundance ranged from Est 1 to 4.7 × 105 CFU 100 ml-1 to Est 1 to 4.1 × 105 CFU 100 ml-1 with phylogenetic group B1 (46.72 %) and A (34.39 %) being most predominant. The prevalence of multiple antibiotic resistance phenotypes of E. coli with the presence of tet and sul resistance genes was higher in wastewater effluents compared to river waters. These findings suggested that E. coli could be an important carrier of resistance genes in freshwater river environments. The phylogenetic composition of E.coli and resistance genes were associated with physicochemical properties and antibiotic residues. These findings indicated that anthropogenic inputs exerted an effect on E. coli phylogroup composition, diversification of multiple antibiotic resistance phenotypes, and the distribution of resistance genes in Larut River.